الدور العسكري والسياسي للقائد المقدوني بيرديكاس : في عهد الاسكند الاكبر - صافي ازهار; موسى رويدة (مجلة دراسات في التاريخ والآثار, 2026)
Perdiccas represents a model of the Macedonian commander whose political identity was shaped by his military experience under Alexander the Great Rising from the Macedonian aristocracy he advanced through the ranks during the Asian campaigns playing a significant role in the operations that consolidated Macedonian control over Anatolia including the Siege of Halicarnassus the Battle of Issus and the Battle of Gaugamela These military achievements elevated his standing within the high command and positioned him for political prominence After Alexander’s death in 323 BCE, Perdiccas emerged as a central figure in the succession crisis, assuming the regency and deriving legitimacy from both the army and his proximity to the late king In his effort to strengthen his authority, he adopted dynastic marriage politics, seeking to link effective power with royal legitimacy through alliance with the Argead house. This strategy, however, alarmed rival commanders and accelerated divisions among them, contributing to the outbreak of the Wars of the Successors Perdiccas’ career thus illustrates the close interaction between military authority and political ambition during the transformation from a unified empire to a system shaped by competing Hellenistic power